The Impact of Social Media on English Language Learning: A Mixed-Methods Study - Ningrum, Putri Kusuma; Apoko, Tri Wintolo (International Journal of Research in Education, 2025)
This study aims to analyze the impact of social media usage on English language learning among high school students, employing a mixed-methods approach. The research focuses on popular social media platforms such as Instagram, TikTok, Twitter, and YouTube, involving 64 tenth-grade students from a high school in Jakarta. In collecting quantitative data, a questionnaire was employed to measure the students’ perceptions of social media. To collect qualitative data, semi-structured interview was used, then analyzed with a thematic analysis. The findings indicate that social media positively contributes to the enhancement of vocabulary, speaking skills, and students' motivation to learn. However, challenges remain, including distractions from non-educational content and a lack of structured learning. The findings emphasize the importance of thoughtfully and specifically incorporating social media into the English language curriculum.